Synthesis of silver nanoparticles using fresh bark of Pongamia pinnata and characterization of its antibacterial activity against gram positive and gram negative pathogens; Resource-Efficient Technologies; Vol. 2, Iss. 1 - Rajeshkumar S. (2016, 2016)
Title screen